2021
DOI: 10.1002/jbm.a.37258
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced corrosion resistance and reduced cytotoxicity of the AZ91 Mg alloy by plasma nitriding and a hierarchical structure composed of ciprofloxacin‐loaded polymeric multilayers and calcium phosphate coating

Abstract: Much effort has made to lessen the cytotoxicity and enhance the corrosion resistance of biodegradable magnesium alloys, for example, by depositing multilayered polymeric coatings containing hydroxyapatite. In this work, a hierarchical structure composed of ciprofloxacin (Cip)‐loaded on polyacrylic acid (PAA) and poly (ethyleneimine) (PEI) as biocompatible polymeric multilayers and calcium phosphate coating as the top layer is formed by the sol–gel method on the AZ91 Mg alloy with an intermediate layer formed b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 43 publications
(214 reference statements)
0
6
0
Order By: Relevance
“…Ma et al and Shanaghi et al suggest that nitridation of coatings on Mg and Al alloys has a positive influence on their corrosion resistance. 33,36 Thus, we attribute the slightly reduced corrosion resistance of Mg-B and Al-B alloys to their physical characteristics.…”
Section: ■ Results and Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Ma et al and Shanaghi et al suggest that nitridation of coatings on Mg and Al alloys has a positive influence on their corrosion resistance. 33,36 Thus, we attribute the slightly reduced corrosion resistance of Mg-B and Al-B alloys to their physical characteristics.…”
Section: ■ Results and Discussionmentioning
confidence: 93%
“…These results suggest that the addition of nitrogen-containing compounds to the bath chemistry improved the degree of crystallinity of magnesium oxide in the coating. We hypothesize that the arc energies generated during aminophenol-enhanced PEO treatment of AZ80 alloys are sufficiently high for the formation of Mg 3 N 2 in the coating chemistry . The appearance of magnesium oxynitride in the coating chemistry could suggest that the localized arc energies are capable of nitriding MgO.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Polyelectrolytes have recently attracted attention by inciting Ca–P conversion coatings on Mg alloys as they facilitate heterogeneous nucleation of Ca–P precipitates with uniform coating deposition. Shanaghi et al [ 134 ] reported that the Ca–P layer deposited on PAA-coated AZ91 Mg alloy significantly improves the osseointegration response. Using a special heat treatment, yang et al [ 135 ] developed a defect-free SiO 2 /PAA coating that acts as a template for mineralizing Ca–P layers on AZ31 Mg alloy.…”
Section: Coatings and Their Current Statusmentioning
confidence: 99%
“…28,29 Many studies have been focused on the layer-by-layer deposition of AZ91 Mg alloy with polymer coating for orthopedic applications. [30][31][32][33][34] However, only a few studies have been focused on the layer-by-layer technique deposition on AZ91 Mg alloy and its systematic physicochemical and biological characterization for cardiovascular stent applications.…”
mentioning
confidence: 99%